Restructuring of the male mice peripheral circadian network after bariatric surgery. Issue 2 (28th June 2021) - Neumann, Anne-Marie; Geißler, Cathleen; Pilorz, Violetta; Olejniczak, Iwona; Lewis, Alfor G; Seeley, Randy J; Shomroni, Orr; Salinas-Riester, Gabriela; Kirchner, Henriette; Oster, Henrik
Abstract : Bariatric surgery is still the most effective long-term weight-loss therapy. Recent data indicate that surgical outcomes may be affected by diurnal food intake patterns. In this study, we aimed to investigate how surgery-induced metabolic adaptations (i.e. weight loss) interact with circadian clock function. For that reason, vertical sleeve gastrectomy (VSG) was performed in obese mice and rhythms in behavior, tissue rhythmicity, and white adipose tissue transcriptome were evaluated. VSG under constant darkness conditions led to a maximum weight loss of 18% compared to a loss of 3% after sham surgery. Post-surgical weight development was characterized by two distinct intervals of catabolic and subsequent anabolic metabolic state. Locomotor activity was not affected. However, VSG significantly increased active phase meal frequency in the anabolic state. No significant effects on clock gene rhythmicity were detected in adrenal and white adipose tissue (WAT) explant cultures. Transcriptome rhythm analyses of subcutaneous WAT revealed a reduction of cycling genes after VSG (sham: 2493 vs VSG: 1013) independent of sustained rhythms in core clock gene expression. This may be a consequence of weight loss-induced morphological reconstruction of WAT that overwrites the direct influence of the local clock machinery on the transcriptome. However, VSG altered rhythmic transcriptional regulation of WAT lipid metabolism pathways. Thus, our data suggest a reorganization of diurnal metabolic rhythms after VSG downstream of the molecular clock machinery.